Design of the star-shaped tip pruning device for broad-leaved tall-stemmed crops based on UAV payload and optimization of its operation parameters - Li, Lianhao; Ma, Guozhen; Liu, Xiaoyong; Zhu, Chenhui; Sun, Qiantao; Qin, Weihua; Jia, Zhimin; Wen , Zhijing (International Journal of Agricultural and Biological Engineering, 2026)
In mountainous and hilly areas, the tip pruning and flower removal operations for broad-leaved tall-stemmed plants are labor-intensive tasks. It is vital for reducing labor costs of broad-leaved tall-stemmed plants to mechanize this operation. To deal with this problem, a tip pruning device which utilizes an unmanned aerial vehicle (UAV) as a carrier to autonomously locate and target broad-leaved tall-stemmed plants is designed in this paper. Firstly, the primary mechanical properties of broad-leaved tall-stemmed plants at full bloom are explored, laying the groundwork for subsequent device design (tobacco is the primary crop studied). Then, the shape and key parameters of the cutting tool for the UAV-mounted tip pruning device, as well as the key parameters of the rhomboid retractable component, are defined based on dynamic analysis, which satisfy demand for the tip pruning device operation. Finally, an adaptive control system for the tip pruning device is developed. The optimization experiments of operational parameters indicate that when the UAV travels at a speed of 0.8 m/s and the tip pruning blade rotates at 1200 r/min, the tip pruning integrity rate exceeds 98.2%, which shows excellent operational performance and the ability to meet actual production demands. This study has significant implications for improving the mechanization and intelligence of tip pruning and flower picking operations in high stem plants. Keywords: broad-leaved tall-stemmed plants; tip pruning device; star-type; terminal bud; unmanned aerial vehicle DOI: 10.25165/j.ijabe.20261901.9863 Citation: Li L H, Ma G Z, Liu X Y, Zhu C H, Sun Q T, Qin W H, et al. Design of the star-shaped tip pruning device for broad-leaved tall-stemmed crops based on UAV payload and optimization of its operation parameters. Int J Agric & Biol Eng, 2026;19(1): 108–119.